Differential toxicity of potentially toxic elements to human gut microbes. (September 2022) - Bolan, Shiv; Seshadri, Balaji; Kunhikrishnan, Anitha; Grainge, Ian; Talley, Nicholas J.; Bolan, Nanthi; Naidu, Ravi
Abstract: Specific microorganisms in the human gut (i.e., gut microbes) provide mutually beneficial outcomes such as microbial balance by inhibiting the growth of pathogenic organisms, immune system modulation, fermentation of ingested products, and vitamin production. The intake of contaminants including potenially toxic elements (PTEs) can occur through food, air, water and some medicines. The gut microbes not only can be affected by environmental contaminants but they themselves can alter the speciation and bioavailability of these contaminants. This research work was designed to demonstrate the relationship between increasing level of selected PTEs including As, Cd, Pb and Hg on the growth of selected gut microbes. The toxicity of above mentioned PTEs to three gut bacteria ( Lactobacillus rhamnosus, Lactobacillus acidophilus and Escherichia coli ) was examined. While the toxicity of all the cationic PTEs including Cd, Pb and Hg towards gut bacteria decreased with increasing pH, the anionic As species exhibited an opposite effect. The order of toxicity was Hg > Cd > Pb > As(III)>As(V) for E. coli ; and Hg > Cd > As(III)>Pb > As(V) for the two Lactobacillus sp. Arsenite (AsIII) showed higher toxicity than arsenate (AsV) to gut bacteria. While As is an anion, Cd, Pb and Hg are cations and hence their binding capacity to the bacterial cell wall varied based on the charge dependent functional groups. However, the toxic effects of PTEs for a bacteria are controlled by their speciation and bioavailability. Graphical abstract: Image 1 Highlights: Gut microbes alter the speciation and bioavailability of potentially toxic elements (PTEs). Potentially toxic elements showed differential toxicity to gut microbes. Toxicity of cationic PTEs (Cd, Pb and Hg) decreased with increasing pH. Arsenite (AsIII) was more toxic than arsenate (AsV) to gut bacteria. PTE toxicity depends on speciation and varied between gut microbes.